A study to assess prevalence of diabetes mellitus and its associated risk factors among adult residents of rural Khammam - Nithesh Kumar, K.; Katkuri, Sushma; Ramyacharitha, I. (International Journal Of Community Medicine And Public Health, 2018)
Background: Type 2 diabetes mellitus is a chronic, debilitating disease characterized by insulin resistance, impaired insulin secretion and hyperglycemia. It represents more than 90% of total prevalence of diabetes in the world and is responsible for 9% of the global mortality corresponding to four million deaths per year. The objective of the study was to assess the prevalence of diabetes mellitus type-2 in a rural population of age 30 years and above. Methods: A community based cross sectional study carried out in population 30 years and above in rural area of Khammam district in Telangana during the study period from 1st January to 31st December 2015. A total of 910 persons aged 30 years or more were included in study. Results: Near about 74 (8.1%) were diagnosed as type -2 diabetes mellitus. The prevalence of DM was 16.22% in 30-40 years age group, 24.32% in 41-50 years age group, 43.34% in 51-60 years age group and 16.2% in 61-70 years age group which shows that DM increases with age and the association between age and prevalence of type 2 DM was found to be statistically significant. Conclusions: There is a need to increase awareness of type–2 diabetes mellitus in the general population. Health education should be given in terms of risk factors of diabetes. They should be made aware about early screening methods.